IDENTIFIKASI FAKTOR RISIKO PENYEBAB STUNTING PADA BALITA - Dwi Lestari; Tri Wahyuni; Ryryn Suryaman Prana Putra; Haesti Sembiring (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Stunting is a chronic nutritional problem characterized by impaired growth and development in children due to prolonged malnutrition, particularly during the first 1,000 days of life (HPK). The objective of this study was to identify risk factors for stunting in toddlers. A cross-sectional study design was used. The study was conducted in the service area of the Mangulewa Community Health Center (Puskesmas). The study was conducted in July 2025. The study population consisted of all toddlers in the Golewa Barat subdistrict. The sample size was 115 toddlers. Simple random sampling was used. A research questionnaire was used as the research instrument. Data analysis was performed using univariate and bivariate methods. The results showed an association between birth spacing (p-value: 0.027) and family income (p-value: 0.015) with the incidence of stunting in toddlers. It is recommended that the community health center conduct routine nutritional examinations and monitoring of toddlers at every Posyandu session.Keywords: Toddlers, Birth Spacing, Family Income.